Pengaruh Keluarga dan Kelompok Referensi Terhadap Keputusan Konsumen Membeli Kosmetika Khusus Pria (Studi Kasus Merek Vaseline Men di Pekanbaru) - Nely Novita; Lilis Sulistyowati; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effects of Family and Group References that consist of Friend Group, Work Group, Purchasing Group, Consumer-Action Group, and Web Group on Purchase Decision of Vaseline Men Cosmetics in Pekanbaru. The samples of this study were taken from Vaseline Men users, which were teenagers and grown men in Pekanbaru. The samples were chosen only Vaseline Men Consumers that buying it by themshelves (not gifting or presents), and consumers that at least 17 years old above to fill the questionnaires. The data analysis used were multiple linear regression analysis with the help of SPSS ver. 20. The results of the test showed that not all of the variables had a significant effect on Purchase Decision of Buying the Vaseline Men Cosmetics in Pekanbaru. Only Purchasing Group and Consumers-Action Group had a significant effect on Purchase Decision of Buying the Vaseline Men in Pekanbaru.Keywords: Family, Friends Group, Works Group, Purchasing Group, Consumers-Action Group, Web Group, Purchase Decision of Buying of Vaseline